Investigation of the skin microbiome: swabs vs. biopsies. (1st September 2019) - Prast‐Nielsen, S.; Tobin, A.‐M.; Adamzik, K.; Powles, A.; Hugerth, L.W.; Sweeney, C.; Kirby, B.; Engstrand, L.; Fry, L.
Summary: Background: Human skin is populated by diverse bacteria and there is increasing evidence that resident bacteria play a key role initiating immune responses in cutaneous diseases such as atopic dermatitis, psoriasis and hidradenitis suppurativa. Bacteria are present at all layers of the skin but many studies have relied on swabs to profile the skin microbiota. Objectives: As the pathogenesis of many skin conditions is dermal, we wanted to compare the microbiota obtained in swabs (surface) and biopsies (dermis). Methods: Using 16S rRNA gene sequencing we established the microbial profiles of skin swabs and skin biopsies in 16 patients. Results: We found differences in both diversity and taxonomic composition of the microbiome obtained from swabs and biopsies of the same individual. Several taxa were found to be more abundant in the swabs, which displayed significantly higher community richness, but Clostridiales and Bacteroidetes were significantly enriched in the biopsies. Most published research on cutaneous microbiota has been based on skin swabs, which represent the surface of the skin. Conclusions: Our study demonstrated a clear difference between the microbiome observed from skin swabs and skin biopsies. These findings may be highly relevant in disorders such as psoriasis where pathogenesis arises in the dermis. What's already known about this topic? 16S RNA gene sequencing has facilitated study of the skin microbiome. Several studies have sequenced the microbiome sampled by skin swabs. What does this study add? The microbiome data obtained using swabs and biopsies were different. Diseases that are predominantly dermal should be studied using both swabs and biopsies.